Peran Kepemilikan Kartu Kredit Dalam Memoderasi Pengaruh Kontrol Diri dan Atmosfer Gerai Terhadap Perilaku Belanja Kompulsif Konsumen Pakaian di Kuta-Bali - Kurniawan, Florentine Yovita; Suparna, gede (E-Jurnal Manajemen, 2014)
Knowing the role of credit card ownership in moderating influence of self-control and atmospheric outlets to consumers compulsive buying clothes in Kuta, is the objective of this research activity. Data were collected through questionnaires with Likert Scale, the 110 respondents who were in Mall Bali Galeria and Beachwalk, Kuta. Samples were obtained using a purposive sampling technique . The data has been obtained , then analyzed using the Moderated Regression Analysis ( MRA ) in which the classical assumption test before use to avoid the occurrence of deviations. Based on the research results, it is concluded that self-control and a significant negative effect on consumer compulsive buying clothes, the atmosphere and store credit cards and a significant positive effect on consumer compulsive buying of clothing, as well as credit card ownership proved to moderate the effect of self-control and the behavior of atmospheric outlet compulsive spending consumer apparel. Credit card is able to amplify the negative effect of self-control and weaken the positive effect of atmospheric outlets to consumers compulsive buying clothes . Keywords : credit card ownership , self-control , atmospheric outlets , compulsive buying Normal 0 false false false st1\:*{behavior:url(#ieooui) } /* Style Definitions */ table.MsoNormalTable {mso-style-name:"Table Normal"; mso-tstyle-rowband-size:0; mso-tstyle-colband-size:0; mso-style-noshow:yes; mso-style-parent:""; mso-padding-alt:0in 5.4pt 0in 5.4pt; mso-para-margin:0in; mso-para-margin-bottom:.0001pt; mso-pagination:widow-orphan; font-size:10.0pt; font-family:"Times New Roman"; mso-ansi-language:#0400; mso-fareast-language:#0400; mso-bidi-language:#0400;}